CLASSROOM ACTION RESEARCH IMPLEMENTATION IN SECONDARY SCHOOLS. - Dagnew kelkay, Asrat (International Journal of Psychosocial Rehabilitation, 2021)
The Purpose of this study was to assess classroom action research implementation at secondary schools. A Mixed research methods approach was employed. Six sample schools with 222 teachers were selected as a target population. Questionnaire, focused group discussion, interview and classroom observation were used as instruments of data collection. The data was collected randomly from 122 teachers, 6 schools principals, 3 supervisors and 3 district education experts. Cronbach Alpha values were 0.833 for action research implementation level, 0.927 role played by principals in facilitating action research, 0.866 for hindering factors and 0.875 for overall implementation of action research measure of reliability test. Both descriptive and inferential statistics analysis techniques were used to compute the data. The findings of the study indicated that secondary school teacher’s implementation of action research was low. Role played by principals in facilitating action research in secondary school teachers’ were not significantly a modeling role.